Government Debt Issuance in the Euro Area : The Impact of the Financial Crisis. (IMF Working Papers; Working Paper ;, 2011)
This paper documents and analyzes crisis-related changes in government debt issuance practices in the 16 euro zone countries and Denmark. Using a newly constructed database on primary market debt issuance during 2007-09, we find evidence of a shift away from pre-crisis standards of best funding practices competitive auctions of debt instruments with a fixed coupon, long maturity and local currency denomination (DLTF). Exploiting the cross-country panel data dimension of the data, we conclude that the crisis and related changes in the macroeconomic environment and investor sentiment can account for a significant proportion of the deviation. The negative effect of the crisis on DLTF debt issuance was especially pronounced in high deficit and high debt euro area countries, and has forced governments to assume additional risk.